2011
DOI: 10.1534/genetics.110.125708
|View full text |Cite
|
Sign up to set email alerts
|

The Yak1 Protein Kinase Lies at the Center of a Regulatory Cascade Affecting Adhesive Growth and Stress Resistance inSaccharomyces cerevisiae

Abstract: In Saccharomyces cerevisiae, adhesive growth on solid surfaces is mediated by the flocculin Flo11 to confer biofilm and filament formation. Expression of FLO11 is governed by a complex regulatory network that includes, e.g., the protein kinase A (PKA) signaling pathway. In addition, numerous regulatory genes, which have not been integrated into regulatory networks, affect adhesive growth, including WHI3 encoding an RNA-binding protein and YAK1 coding for a dual-specificity tyrosine-regulated protein kinase. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 69 publications
3
63
0
Order By: Relevance
“…We have previously shown that Whi3 is able to control biofilm development by both post-transcriptional control of Yak1 and yet unknown, Yak1-independent mechanisms (Malcher et al 2011). We therefore wanted to know whether Whi3 is able to control additional yeast developmental regulators at the post-transcriptional level.…”
Section: Whi3 Controls Key Regulators Of Yeast Development At the Posmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that Whi3 is able to control biofilm development by both post-transcriptional control of Yak1 and yet unknown, Yak1-independent mechanisms (Malcher et al 2011). We therefore wanted to know whether Whi3 is able to control additional yeast developmental regulators at the post-transcriptional level.…”
Section: Whi3 Controls Key Regulators Of Yeast Development At the Posmentioning
confidence: 99%
“…The RNA recognition motif (RRM) protein Whi3 is another RNA-binding protein that controls S. cerevisiae adhesion and biofilm formation. In contrast to Mpt5, Whi3 activates these processes and targets the dual-specificity tyrosine-regulated protein kinase Yak1 (Mösch and Fink 1997;Malcher et al 2011). Specifically, Whi3 controls production of Yak1 at the post-transcriptional level, which in turn activates expression of FLO11, a cell surface flocculin for adhesion and biofilm formation, via the transcription factors Sok2 and Phd1 (Gimeno and Fink 1994;Ward et al 1995;Lo and Dranginis 1998;Guo et al 2000;Pan and Heitman 2000;Reynolds and Fink 2001;Malcher et al 2011).…”
mentioning
confidence: 99%
See 3 more Smart Citations